MCM3AP-AS1: An Indispensable Cancer-Related LncRNA - Yu, Xiao; Zheng, Qingyuan; Zhang, Qiyao; Zhang, Shuijun; He, Yuting; Guo, Wenzhi (Frontiers in Cell and Developmental Biology, 2021)
Long noncoding RNAs (lncRNAs) are a class of RNA molecules with transcript lengths longer than 200 nucleotides that have no protein-coding ability. MCM3AP-AS1, a novel lncRNA, is aberrantly expressed in human cancers. It is significantly associated with many clinical characteristics, such as tumor size, TNM stage, and pathological grade. Additionally, it considerably promotes or suppresses tumor progression by controlling biological functions of cells. MCM3AP-AS1 is a promising biomarker for the diagnosis, prognosis, and treatment of cancer. In this review, we briefly summarize the published studies on the expression, biological function, and regulatory mechanisms of MCM3AP-AS1. We also discuss the clinical applications of MCM3AP-AS1 as a biomarker.